2000
DOI: 10.1128/jcm.38.11.4000-4005.2000
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an Immunocapture-Agglutination Test (Brucellacapt) for Serodiagnosis of Human Brucellosis

Abstract: We evaluated the validity and the usefulness of a new test for the diagnosis of human brucellosis based on an immunocapture-agglutination technique. A total of 315 sera from 82 patients with a diagnosis of brucellosis, 157 sera from patients in whom brucellosis was suspected but not confirmed, and 412 sera from people living in rural areas with endemic brucellosis were studied. The seroagglutination test (SAT), Coombs anti-Brucella test, and Brucellacapt test were evaluated. All the initial sera from the 82 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0
6

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(71 citation statements)
references
References 27 publications
2
63
0
6
Order By: Relevance
“…The rose Bengal plate agglutination test, Wright's seroagglutination, Coombs anti‐brucella test and indirect immunofluorescence were performed as described previously [11–13]. The immunocapture‐agglutination test (Brucellacapt; Vircell SL, Santa Fé, Spain) was performed according to the manufacturer's instructions [14].…”
Section: Methodsmentioning
confidence: 99%
“…The rose Bengal plate agglutination test, Wright's seroagglutination, Coombs anti‐brucella test and indirect immunofluorescence were performed as described previously [11–13]. The immunocapture‐agglutination test (Brucellacapt; Vircell SL, Santa Fé, Spain) was performed according to the manufacturer's instructions [14].…”
Section: Methodsmentioning
confidence: 99%
“…All isolates were sent to the National Brucellosis Reference Laboratory in Valladolid, Spain, for definitive identification and biotyping. The rose Bengal agglutination test and Wright's seroagglutination test were performed as described previously [14], and the immunocapture-agglutination test (Brucellacapt; Vircell SL, Sante Fé, Spain) was performed according to the manufacturer's instructions [15].…”
Section: Negative Control Groupmentioning
confidence: 99%
“…This test is based on an immunocapture agglutination technique and detects nonagglutinating IgG and IgA antibodies, as well as agglutinating antibodies (11). Studies revealed that the specificity and sensitivity of CAT and ICAT methods were similar and, hence, both could be preferred to verify SAT (14,15). Brucella Coombs gel test is a new agglutination-based serologic test, which is practical, and yields results within 2 h. Irvem et al reported that the gel test method showed excellent correlation with both CAT and ICAT tests (16).…”
Section: Diagnosismentioning
confidence: 99%